Revealing How Enterpreneurial Motivation Affects Business Success through Entrepreneurial Competence As Intervening Variable - Destiana; Jufri Yandes; Muhtarom; Dedy Juniadi (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2024)
Actors of MSMEs have an essential role in encouraging economic growth, especially MSMEs in creative economy. They have a role in labor absorption. The success of the MSMEs business is not only limited to understanding the external factor, but the most important thing is also from the internal factor. Entrepreneurial motivation and entrepreneurial competence are internal factors that MSMEs need to have. These internal factors are the main points that must be understood as internal strengths to achieve business success. This study aimed to determine and explain the effect of entrepreneurial motivation on entrepreneurial competence and its impact on business success. The type of research used was descriptive quantitative with 120 respondents. Data is collected by delivering questionnaires through Google Form to MSME owners, utilizing a Likert scale. Researchers utilized the SmartPLS 3 application and set a significance level of 0.05 for data analysis. The research findings indicate that entrepreneurial motivation positively and significantly influences entrepreneurial competence. However, entrepreneurial motivation does not significantly impact business success. On the other hand, entrepreneurial competence positively and significantly affects business success. Additionally, entrepreneurial motivation positively and significantly contributes to business success through entrepreneurial competence.